Adolescents perceptions and behaviors towards periodic health examinations in Riyadh, Saudi Arabia - Mohammed Alrukban; Ahmad Alsultan; Alwaleed Alnasser; Ahmed Alayban; Mohammed Almousa; Salman AlOtaibi; Shaffi Ahamed Shaik (BMC Public Health)
Abstract Objectives To evaluate and assess the awareness, knowledge, and level of application of recommended Periodic Health Examinations (PHEs) for adolescents in Riyadh. Methods Descriptive Cross-sectional study, conducted among adolescents between June 2022 and January 2023. The Sample size was 1199 adolescents of both genders, between the ages of 12–20 years, studying in intermediate and secondary schools in Riyadh. The sample of participants was collected through a stratified multistage random sampling technique. Ethical approval and Ministry of Education acceptance were considered. The data was collected using a structured, self-administered questionnaire containing close-ended questions. The level of knowledge was assessed by using three knowledge items; PHE definition, PHEs performance time, and the list of recommended PHEs known. The level of performance was assessed based on the performance of recommended (Six recommended PHEs by Saudi CDC) and none-recommended (Nine non-recommended PHEs as distractors). Results Among the (1199) adolescents, the vast majority (70.6%) were aware of the PHEs. There is a positive attitude of adolescents toward PHEs, with (75.8%) acknowledging their importance and (87.1%) willing to undergo PHEs if given the opportunity. Despite this positive attitude, the actual knowledge and performance of PHEs remains relatively low, with (56.1%) being illiterate about it and only (36.8%) having undergone PHEs at least once, and a smaller percentage (26.1%) doing so regularly. There was a clear association (p < 0.05) between the level of knowledge and application. Adolescents with adequate knowledge had a higher prevalence of application (56.8% VS 43.2%). There was an association between Adolescents'level of education and their levels of knowledge and performance (p < 0.05). The more educated adolescents the higher their knowledge level and performance level. There was also an association between the availability of health insurance and application. The presence of health insurance increases the probability of applying PHEs. The most used sources of information regarding PHEs were digital sources (62.1%). Conclusion The study concluded that there is a positive attitude of adolescents toward PHEs. The study highlights a disparity in knowledge and performance of PHEs among adolescents, influenced by socio-demographic factors such as gender, nationality, type of school, and parental education. Females and students from private or international schools, as well as those with higher levels of parental education, demonstrated better knowledge and higher performance rates of PHEs. The research underscores the role of digital sources in educating adolescents about PHEs. This study emphasizes the need for targeted educational interventions to improve adolescent knowledge and performance of PHEs, considering the identified barriers and socio-demographic influences.